1997
DOI: 10.1002/(sici)1096-9071(199702)51:2<115::aid-jmv5>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibodies to human caliciviruses (HuCVs) in Kuwait established by ELISA using baculovirus-expressed capsid antigens representing two genogroups of HuCVs

Abstract: Baculovirus recombinant-expressed antigens of Norwalk viruses (rNV) and a Mexico strain (rMX) of the Snow Mountain serogroup of human caliciviruses (HuCVs) were used in enzyme immunoassays to study the antibody prevalence among the Kuwaiti population and foreign workers employed in Kuwait. The antibody titers in 16 different age groups which ranged from neonates to centenarians were investigated by testing eight different dilutions of each serum (1:200-1:25,600). The results indicate that NV infection is wides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This is even more challenging when there are many circulating strains with largely unknown cross-reactivity, multiple infections over a lifetime are likely, and the study subjects are adults. In this situation, setting a low cut-point results in all, or nearly all, samples classified as seropositive, as reported in other norovirus seroprevalence studies [36,37,39,40,[42][43][44][45][46]. To better understand more recent infections and reduce the impact of cross-reactivity, higher cut-points based norovirus human challenge data, were used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This is even more challenging when there are many circulating strains with largely unknown cross-reactivity, multiple infections over a lifetime are likely, and the study subjects are adults. In this situation, setting a low cut-point results in all, or nearly all, samples classified as seropositive, as reported in other norovirus seroprevalence studies [36,37,39,40,[42][43][44][45][46]. To better understand more recent infections and reduce the impact of cross-reactivity, higher cut-points based norovirus human challenge data, were used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative approach to pathogen detection in stool samples, serology is commonly used to estimate the prevalence in a population. Serological studies representing different populations globally have identified a prevalence of antibodies to noroviruses ranging between 80% to 100% in adults (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Most serology studies used virus-like particles (VLPs) of GI.1, GII.3, and GII.4 (8,16,24,25), and only a few have investigated antibody responses to other norovirus genotypes (14,26,27).…”
Section: Introductionmentioning
confidence: 99%